Aplicativo mobile de hotel: um estudo sobre a ótica da cocriação de valor - Pedron, Cristiane Drebes (2021)
The development of information technology (IT) has influenced the tourism and hospitality sector, presenting possibilities for interactions with customers and the co-creation of value. As IT creates opportunities for business-customer interaction, businesses are increasingly relying on mobile technologies to connect with customers. Especially in the hospitality sector, the advancement of technology is providing hotels to develop their own apps, with services based on mobile technologies (e.g. mobile check-in, mobile service requests and mobile keys). In the era of the experience economy, the value perceived by customers of a product or service relies on their consumption experience, which raises a question. Although there is abundant knowledge about the background to the adoption of proprietary apps, research on hotel apps have rarely examined hotel industry professionals’ expectations of hotel services with application to engage customers in value co-creation. Considering this scenario and guided by the dominant service logic, this work aims to answer the following research question: how does the use of the mobile application by the customer allow the co-creation of value in hotel services?To answer this question, a systematic literature review was conducted to investigate the studies produced on value co-creation in the technological context related to the themes of tourism, hospitality, leisure, and culture (phase 1 of this research). Subsequently, an exploratory study with a qualitative approach was carried out, with data collection through semi-structured interviews with professionals in the hotel sector (phase 2 of this research). The interviews were analyzed and coded with the use of the software Atlas ti. The main results pointed to expectations of professionals in the hotel sector about the hotels applications as a means of co-creating value, considering the usefulness of affordances for the client and for the hotel. Therefore, there is a perceived expectation for value, with good practices, strategies, necessary resources, challenges, and limitations of the hotel sector.